2005
DOI: 10.1007/s10804-005-1280-7
|View full text |Cite
|
Sign up to set email alerts
|

Distance, Contact, and Intergenerational Relationships: Grandparents and Adult Grandchildren from an International Perspective

Abstract: In previous studies of intergenerational relationships, geographic distance has been considered the most obvious factor influencing opportunity for frequency of contact between grandparents and grandchildren. This study presents findings from a survey of 70 international college students in the Unites States regarding perceived grandparental influence and relationship satisfaction with their "closest" grandparent. Results showed that participants' perceived influence of grandparents and relationship satisfacti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
0
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(36 citation statements)
references
References 18 publications
2
32
0
1
Order By: Relevance
“…The contribution of emotional support from adolescent and/or adult grandchildren seemed to suggest that the grandparent-adolescent and/or adult grandchildren relationship provides opportunities to fulfill companionship needs for both parties, which was consistent with the literature (Crosnoe and Elder 2002;Taylor et al 2005). Both sides are mutually attached and the grandparents feel supported while interacting with their grandchildren.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…The contribution of emotional support from adolescent and/or adult grandchildren seemed to suggest that the grandparent-adolescent and/or adult grandchildren relationship provides opportunities to fulfill companionship needs for both parties, which was consistent with the literature (Crosnoe and Elder 2002;Taylor et al 2005). Both sides are mutually attached and the grandparents feel supported while interacting with their grandchildren.…”
Section: Discussionsupporting
confidence: 83%
“…It could be associated with both ageinappropriate expectations and cultural-specific role expectations towards grandparents and grandchildren. Last but not the least, while physical distance was not found to be a major barrier for intergenerational relationships, grandchildren support could be better achieved in a context with positive attitudes towards both sides (Taylor et al 2005). Consequently, efforts which are targeted at advocating positive attitude toward older people in Hong Kong are advocated.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Results from three studies support the idea that a strong bond established during childhood positively affects the bond in adulthood. Taylor et al (2005) observed more positive perceptions and greater satisfaction in the intergenerational relationship if adult grandchildren had co-resided with their grandparents during childhood. Brown's (2003) study observed that the quality of adult grandchild-grandparent relationships was higher when a grandparent had intensively cared for their grandchild during childhood.…”
Section: Changes Over Individual Timementioning
confidence: 86%
“…Moreover, previous research indicated the importance of maintaining the link between grandparents and grandchildren across borders (Taylor, Robila, & Lee, 2005). The role of grandparents in immigrant families has been portraied with other immigrant groups as well (e.g., Portes & Rumbaut, 2001).…”
Section: Factors Impacting the Immigration Processmentioning
confidence: 99%